2015
DOI: 10.1016/j.bbamem.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Nanodomain organization of rhodopsin in native human and murine rod outer segment disc membranes

Abstract: Biological membranes display distinct domains that organize membrane proteins and signaling molecules to facilitate efficient and reliable signaling. The organization of rhodopsin, a G protein-coupled receptor, in native rod outer segment disc membranes was investigated by atomic force microscopy. Atomic force microscopy revealed that rhodopsin is arranged into domains of variable size, which we refer to herein as nanodomains, in native membranes. Quantitative analysis of 150 disc membranes revealed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(123 citation statements)
references
References 86 publications
(103 reference statements)
11
112
0
Order By: Relevance
“…Atomic force microscopy (AFM) can provide much needed insights in these areas because it allows for the direct visualization of membrane proteins within the native environment of a lipid bilayer and physiological buffer conditions 1214 . AFM has revealed that rhodopsin is organized into domains within ROS disc membranes that are composed of rows of dimeric receptor 1517 . These domains are referred to as nanodomains since the dimensions are less than 100 nm 17 .…”
mentioning
confidence: 99%
“…Atomic force microscopy (AFM) can provide much needed insights in these areas because it allows for the direct visualization of membrane proteins within the native environment of a lipid bilayer and physiological buffer conditions 1214 . AFM has revealed that rhodopsin is organized into domains within ROS disc membranes that are composed of rows of dimeric receptor 1517 . These domains are referred to as nanodomains since the dimensions are less than 100 nm 17 .…”
mentioning
confidence: 99%
“…Some works argue that even though a membrane is maintained out-ofequilibrium by active processes, equilibrium statistical mechanics is sufficient to account for the finite size of membrane nano-domains [21,18,22,19]. For example, the observation of nano-domains of rhodopsin (a GPCR) in cadavers' retina cells [8], very similar to those observed in fixed cells or membrane sheets, suggests that active processes are not essential. Alternatively, some other works propose that out-of-equilibrium mechanisms are necessarily at play, driven by active membrane recycling [25,29,14,30,31,26,32].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since proteins represent about one half of the membrane mass, the protein surface fraction φ is on the same order of magnitude, even though certainly slightly smaller because many proteins protrude out of the membrane plane. Accepted values lie around φ = 0.2 [8,10]. We shall explore the range φ = 0.01 to 0.3 in this work and the SI.…”
Section: State Of the Art And Modelmentioning
confidence: 99%
See 2 more Smart Citations